Analisis Komparasi Pendapatan Usahatani Karet Berdasarkan Pilihan Penjualan Bahan Olah Karet di Kecamatan Bajubang dan Kecamatan Jambi Luar Kota - Murdy, Saad; Fathoni, Zakky; Farida, Aulia (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2019)
There are several factors that cause the low selling prices of rubber farmers. Most rubber farmers in Jambi Province sell their rubber to collectors, and not directly sell it to rubber factories. The purpose of this study was to compare the income of rubber farming based on the choice of rubber sales, namely traders and non-traders. The scope of this research area is Bajubang District, Batanghari Regency and Jambi Luar Kota Muaro Jambi District. This research was conducted using survey methods, cost and income analysis, and comparative analysis of two different test averages. The average farm income from rubber farmers selling rubber through collectors is Rp. 2,652,357, - / month, with a total fee paid of Rp. 302,857 / month. The average farm farm receipts selling rubber to the auction market is Rp. 3,416,700 / month, with a total fee paid of Rp. 235,951, - / month. While the acceptance of rubber farming businesses that sell rubber to factories through the KUD is Rp. 3,273,975 / month, with a total fee paid of Rp. 463,513, - / month. There is a significant difference between the income of farmers in rubber farming who sell to collectors and the auction market. As for the income of rubber farming farmers who sell to collectors and farmers who sell to factories there is no significant difference. Keywords: Collector Traders, Non Collector Traders, Income